Budget-neutral fiscal rules targeting inflation differentials - Maren Brede (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
In light of persistent in ation dispersion and rising debt levels in the EMU, this paper investigates the welfare implications of budget-neutral scal policies that counteract in ation di erentials. In a two-country DSGE model of a monetary union with traded and non-traded goods a national scal authority is able to reduce welfare losses arising from asymmetric shocks by following a Taylor-type rule for consumption taxes while using labour income taxes to balance its budget. Under technology and government spending shocks welfare losses can be reduced by up to 15%.
Keywords: E62; E63; F41; F45; 330; inflation differentials; monetary union; fiscal policy; budget-neutral policy